Challenges and Opportunities Implemented in Preventing Corruption Criminal Actions - Mohd. Yusuf DM; Geofani Milthree Saragih (Journal of Law Science, 2022)
In the field of education, people are currently faced with formal and informal education such as anti-corruption which is integrated into basic education to higher education. sometimes, sanctions or punishments have no fundamental effect on the harm and are only temporary. Referring to China, although corruptors are shot dead by cruel executions, the corruption rate continues to increase. The main issue discussed in this study is whether corruption prevention is better than punishment and corruption prevention strategies. This type of research is legal research whose research is based on secondary data. Research sources are taken from reference books, laws, expert opinions, and all supporting resources in carrying out legal research. In conclusion, corruption is a despicable and vile behavior that stems from low morality and a person's lack of shame. Corruptors have done everything possible for themselves or others; shows that corruption can be classified as an extraordinary crime. To prevent corruption, government officials and officials must have a strong will to fight moral greed.